The pentameric vertex proteins are necessary for the icosahedral carboxysome shell to function as a CO2 leakage barrier. - Fei Cai (Public Library of Science (PLoS), 2009)
Background Carboxysomes are polyhedral protein microcompartments found in many autotrophic bacteria; they encapsulate the CO(2) fixing enzyme, ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) within a thin protein shell and provide an environment that enhances the catalytic capabilities of the enzyme. Two types of shell protein constituents are common to carboxysomes and related microcompartments of heterotrophic bacteria, and the genes for these proteins are found in a large variety of bacteria. Methodology/principal findings We have created a Halothiobacillus neapolitanus knockout mutant that does not produce the two paralogous CsoS4 proteins thought to occupy the vertices of the icosahedral carboxysomes and related microcompartments. Biochemical and ultrastructural analyses indicated that the mutant predominantly forms carboxysomes of normal appearance, in addition to some elongated microcompartments. Despite their normal shape, purified mutant carboxysomes are functionally impaired, although the activities of the encapsulated enzymes are not negatively affected. Conclusions/significance In the absence of the CsoS4 proteins the carboxysome shell loses its limited permeability to CO(2) and is no longer able to provide the catalytic advantage RubisCO derives from microcompartmentalization. This study presents direct evidence that the diffusion barrier property of the carboxysome shell contributes significantly to the biological function of the carboxysome.